2015
DOI: 10.1002/piq.21196
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Skills Needed by Instructional Designers in Higher Education

Abstract: In this paper, we sought to address the following research question: What knowledge and skills are needed by instructional designers in higher education to be successful in their roles? We interviewed eight instructional designers from across the United States, all working for institutions of higher education. Using the constant comparative method, we analyzed our data to identify relevant themes. Our results suggest that instructional designers in higher education must have a solid foundation in instructional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 23 publications
5
94
0
1
Order By: Relevance
“…Similar to previous studies (Pan et al, 2003;Richardson et al, 2019;Ritzhaupt & Kumar, 2015), the faculty in this study also had misconceptions about the role of IDs in this mentorship process. IDs were perceived as technical personnel in charge of technology and placing the course content online.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Similar to previous studies (Pan et al, 2003;Richardson et al, 2019;Ritzhaupt & Kumar, 2015), the faculty in this study also had misconceptions about the role of IDs in this mentorship process. IDs were perceived as technical personnel in charge of technology and placing the course content online.…”
Section: Discussionsupporting
confidence: 82%
“…Following previous studies (Kumar & Ritzhaupt, 2017;Richardson et al, 2019;Ritzhaupt & Martin, 2014), this study found evidence of the importance IDs' soft skills in building trust or gaining "buy-in" (Ritzhaupt & Kumar, 2015) with university faculty during mentorship relationships. Moreover, when IDs have strong persuasive skills, relationship-building skills, and communication skills (Ritzhaupt & Kumar, 2015), they can help faculty members become successful in teaching high-quality online courses. When working with university faculty who are new to online course design and development, it is very important that IDs are equipped with strong skills to teach them and are able to explain complex learning design elements (Ritzhaupt & Kumar, 2015).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The success of distance education therefore depends on the ability of instructional designers to provide student satisfaction and retention (Saba, 1999). Accordingly, instructional designers in distance education should have a broad background in instructional design and distance learning theory, have both technical and soft skills, and have a willingness to learn emerging information and communication technologies (Ritzhaupt & Kumar, 2015).…”
Section: Introductionmentioning
confidence: 99%